Density Measurement for the Binary Mixtures of Ionic Liquid 1-ethyl- 3-methylimidazolium Diethylphosphate and Water (Methanol or Ethanol) at 1atm and (293.15 to 333.15) K - Gong, Yin-Hui; Lu, Ying-Zhou; Meng, Hong; Li, Chun-Xi (Journal of Applied Solution Chemistry and Modeling, 2013)
The density data for the binary mixtures of an ionic liquid (IL), 1-ethyl-3-methylimidazolium diethylphosphate [EMIM][DEP], and water (methanol or ethanol) were measured at 1 atm as a function of composition in the temperature range of (293.15 to 333.15) K using a vibrating-tube densimeter. The excess molar volumes (VE) and other thermodynamic properties were derived from the density data. All VE values are negative for the binary mixtures in the whole composition range, and reach to the maximum at the mole fraction of IL of ca. 0.3. The VE values decrease with increasing temperature for the aqueous solution of ILs, but increase with the increasing temperature for the IL solutions of methanol or ethanol. The excess molar volumes were correlated successfully by an empirical equation with the maximum average absolute relative deviation within 0.02%.